Realisasi Tindak Kesantunan Berbahasa Di Kalangan Tenaga Kependidikan Di SMP Negeri 1 Teras Dan SMA Bhineka Karya 3 Boyolali - Primary, Hendra Ahya, Prof. Dr. Harun, S.H., M.Hum (2014)
This study describe about the acts of politeness forms of realization and fulfillment of follow politeness and students' perception of politeness among educators of SMP Negeri 1 Teras and SMA Bhineka Karya 3. The purpose of this study was to determine how the realization and implementation of follow politeness politeness principle spoken by educators as well as students' perception of politeness used by the educational staff at SMP Negeri 1 Teras and SMA Bhineka Karya 3 Boyolali. This study used a qualitative descriptive method, the data collection techniques in this study using the listening, writing and recording techniques, techniques of data analysis in this study using a unified method ekstralingual. The data source of this research is SMP Negeri 1 Teras and SMA Bhineka Karya 3 Boyolali. In this study utterances used by educational personnel have met the politeness principle of Leech. The results of the realization of linguistic politeness follow everything done and said politely. Being the result of the application of and compliance with the principle of linguistic politeness all available data indicate that what was said and done have fulfilled the maxim theory Wisdom, Generosity, praise, humility, Welfare and sympathy. Students perception to acts of politeness after questionnaire has the result that a lot of students which suggests the utterances of the most frequently used in communication between speakers and opponents said all use polite language.